2014
DOI: 10.5489/cuaj.2337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of penile degloving and proximal ventral dissection on curvature correction in children with proximal hypospadias

Abstract: Introduction: Penile degloving is an important step in orthoplasty. Although its role in correcting mild curvature in distal and midshaft hypospadias has been previously reported, its impact on ventral curvature (VC) correction in proximal defects warrants further investigation. Therefore, we sought to document the effect of degloving and proximal urethral dissection on VC correction in children with proximal hypospadias. Methods: We retrospectively reviewed the records of 137 patients who underwent proximal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The severity of VC should be assessed after thorough degloving and excision of all fibrotic ventral bands of the penis. Degloving alone can improve or correct mild and moderated VC [22]. At the present institution, it is preferable to assess VC without tourniquet, accessing the corpora M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…The severity of VC should be assessed after thorough degloving and excision of all fibrotic ventral bands of the penis. Degloving alone can improve or correct mild and moderated VC [22]. At the present institution, it is preferable to assess VC without tourniquet, accessing the corpora M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…Even for proximal hypospadias, degloving the penis alone can correct the VC, and transection of the UP should be avoided before repeating an artificial erection. Weber et al studied 137 patients with proximal hypospadias and reported that degloving the penis alone was sufficient for VC correction in 7 of 9 (77%) mild cases, 14 of 44 (30%) moderate, and only 2 of 84 (2%) severe cases ( 25 ).…”
Section: High-grade Penile Curvaturementioning
confidence: 99%
“…The release of fibrotic tissue and the dartos fascia with scissors should be performed down to the base of the penis. The correction of the curvature is possible with this maneuver and the transfer of dorsal skin to the ventral aspect of the penis ( 25 ).…”
Section: Key Pointsmentioning
confidence: 99%
“…Chordee was defined as a penile shaft curvature and is categorized based on its degree measured by a goniometer: mild (<30), moderate (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and severe (>45) curvature. 10 The variables were measured and the operations were performed by a single surgeon to remove potential interobserver variations in the measurements and observations and surgical outcomes. The largest point of UP was recorded as the width.…”
Section: Methodsmentioning
confidence: 99%